Numerical simulation of non-newtonian fluid at low reynolds number - Koh, Aldric Boon Wee (2017)
Due to their complicated governing equations which contain more parameters than their Newtonian counterparts, many studies involving non-Newtonian fluids utilize numerical solvers such as ANSYS. Since numerical simulations lacks physical representation, ensuring a proper simulation setup is essential to obtain accurate results. As such, various types of convergence such as iteration convergence and mesh convergence will be analysed. Adding on, simulations will be done to better understand the various simulation parameters and identify the appropriate setup. The capabilities of ANSYS is often limited by its inbuilt functions and User-Defined Functions is one way to bypass this limitation. Hence, various applications of these functions will be featured by introducing and implementing several C codes into ANSYS. C codes containing the power-law model and the Carreau model to describe the non-Newtonian fluid’s viscosity will then be validated to examine the potential of these User-Defined Functions. This study will therefore provide an insight on the feasibilities of adopting User-Defined Functions in numerical simulations and verify that these C codes do not compromise on the numerical accuracy of the solver.